Comparative silver staining patterns of water buffalo, goat, and pig spermatozoa - Bongso, T.A. (Informa UK Limited, 1983)
Spermatozoa from river and swamp water buffalo (Bubalus bubalis), goat, and pig were stained using a silver nitrate procedure and examined under bright field optics. The silver nitrate differentiated many detailed morphologic features of the head, midpiece, and tail of spermatozoa between the species studied. Acrosomal integrity due to sperm injury or aging and various sperm abnormalities were also clearly identified by silver nitrate. Silver staining patterns revealed species-specific and strain-specific differences, particularly of the sperm head. The biochemical basis of silver staining has been attributed to the presence of sulphydryl and disulphide-rich proteins. The technique is relatively inexpensive, rapid, and repeatable and may be useful for biological research and evaluation of semen for artificial insemination.